Engineering Assessment of the Soils of Modern Residential Complexes (Bety, Yarmouk, and Al-Jawhara) in Tikrit/Salah Al-din/Iraq - Salah, Laith Ikhlas; Alhadad, Khaled Ahmed Abdullah (Iraqi Journal of Science, 2022)
In this research, the geotechnical properties of soil for modern residential complexes in the city of Tikrit-Iraq were determined using six samples represented by three residential complexes (Bety, Yarmouk and Jawhara) and that these complexes built on gypsum soils suffer in the future from several engineering problems that appear in the form of cracks, inclination or subsidence in The buildings or the collapse of the facilities, the dilution of the roads and the breaking of the water and sewage networks due to the melting of the gypsum in the soil. One of the most important objectives for the research is that the residential complexes for the research area in Tikrit are not older than some years. With the urban expansion that all towns in Iraq are witnessing, including this region, the city of Tikrit represents the center of the province. Therefore most of the departments and institutions are present in this region, which necessitated the need to provide residential complexes and many of the constituencies’ employees to occupy them in addition to its proximity to the University of Tikrit, so it is necessary to know the properties of soil, to point out the engineering problems in it and how to address them. As well, it is an important region from a geographical point of view because it is located directly on the main international road linking Baghdad - Tikrit – Mosul The moisture content values of the soil samples range from (0.92 to 0.26%). The resultant values ​​are low because one of the reasons is that the sampling process took place in the summer, specifically in July, and the reason is due to the low level of groundwater in the region, as well as the high temperature and the lack of rainfall, which causes the evaporation of the water in the soil, so the low moisture content gives a positive concerning the foundations of residential complexes in the study area because the presence of water causes the dissolution of gypsum as the soil under study contains a high percentage of gypsum. The calculated specific gravity values of soil samples range from 2.42 to 2.46 with an average of 2.42, The average specific gravity is 2.42 in the Bety and Yarmouk, and it is 2.46 in Aljawhara. The maximum dry density values of the soils of the residential complexes range between (1.611-1.663 gm/Cm 3( and the highest dry bulk density value was recorded in the sample (Y1). On the other hand, the optimum moisture content values range between 15.2% and 16.8%, while the highest value is for the sample )B2(. The consolidation test was performed on three selected samples (B2, J1, J2), ((A correction was made for the selection of samples to consolidation test based on the clay ratio, as was the case with the sieving analysis)) based on their clay content percentage compared to other samples which contain low or very clays, The compression index values (Cc) and the bulge index values (Cr) of these samples ​​are (0.084,0.114,0.092) and (0.012,0.013,0.009) respectively. The chemical analyses of the soil in the study area indicates that it contains a high percentage of gypsum that ranges between 43.05 and 69.27. % The gypsum content reaches the highest value in sample (B2) and lowest in sample J2. While the soluble salts percentage range from 73.13)to 85.21%), and the pH value ranges between 7.21and 7.67. Mineralogical, tests of indicate that most samples have prismatic gypsum crystals with several clinker substances, carbonate and evaporites cement and organic materials. The gypsum crystals range in size from 0.02 to 0.7mm with an amount of clay.